Disentangling the cause of a catastrophic population decline in a large marine mammal. Issue 10 (1st October 2015) - Baylis, Alastair M. M.; Orben, Rachael A.; Arnould, John P. Y.; Christiansen, Fredrik; Hays, Graeme C.; Staniland, Iain J.
Abstract : Considerable uncertainties often surround the causes of long‐term changes in population abundance. One striking example is the precipitous decline of southern sea lions (SSL; Otaria flavescens ) at the Falkland Islands, from 80 555 pups in the mid 1930s to just 5506 pups in 1965. Despite an increase in SSL abundance over the past two decades, the population has not recovered, with the number of pups born in 2014 (minimum 4443 pups) less than 6% of the 1930s estimate. The order‐of‐magnitude decline is primarily attributed to commercial sealing in Argentina. Here, we test this established paradigm and alternative hypotheses by assessing (1) commercial sealing at the Falkland Islands, (2) winter migration of SSL from the Falkland Islands to Argentina, (3) whether the number of SSL in Argentina could have sustained the reported level of exploitation, and (4) environmental change. The most parsimonious hypothesis explaining the SSL population decline was environmental change. Specifically, analysis of 160 years of winter sea surface temperatures revealed marked changes, including a period of warming between 1930 and 1950 that was consistent with the period of SSL decline. Sea surface temperature changes likely influenced the distribution or availability of SSL prey and impacted its population dynamics. We suggest that historical harvesting may not always be the "smoking gun" as is often purported. Rather, our conclusions support the growing evidence for bottom‐up forcing on the abundance of species at lower trophic levels (e.g., plankton and fish) and resulting impacts on higher trophic levels across a broad range of ecosystems.